Le avventure di Alice tra controllo e cambiamento. Una rilettura pedagogica del classico di L. Carrol - Demozzi, Silvia (Studi sulla Formazione/Open Journal of Education, 2009)
The essay gives a second reading of Carrol’s classics trought the examination of some categories as control and change. The pedagogical proposal reconsiders some existentials and educative abilities with particular attention to youthful context.